Genomic insights into the clonal reproductive Opuntia cochenillifera: mitochondrial and chloroplast genomes of the cochineal cactus for enhanced understanding of structural dynamics and evolutionary implications - Liu, Jing; Feng, Yuqing; Chen, Cheng; Yan, Jing; Bai, Xinyu; Li, Huiru; Lin, Chen; Xiang, Yinan; Tian, Wen; Qi, Zhechen; Yu, Jing; Yan, Xiaoling (Frontiers in Plant Science, 2024)
The cochineal cactus (Opuntia cochenillifera), notable for its substantial agricultural and industrial applications, predominantly undergoes clonal reproduction, which presents significant challenges in breeding and germplasm innovation. Recent developments in mitochondrial genome engineering offer promising avenues for introducing heritable mutations, potentially facilitating selective sexual reproduction through the creation of cytoplasmic male sterile genotypes. However, the lack of comprehensive mitochondrial genome information for Opuntia species hinders these efforts. Our study addresses this gap by assembling and analyzing the mitochondrial genome of O. cochenillifera, focusing on its structure, repetitive sequences, RNA editing events, inter-organelle gene transfer, and phylogenetic relationships. The mitochondrial genome of O. cochenillifera spans 1,156,235 bp with a GC content of 43.06%, featuring 54 unique protein-coding genes and 346 simple sequence repeats. Comparative genomic analysis revealed 48 homologous segments shared between the mitochondrial and chloroplast genomes, totaling 47,935 bp in length. Additionally, the comparison of mitochondrial genomes from four Cactaceae species highlighted their dynamic nature and frequent mitogenomic reorganizations. These findings offer valuable insights into the mitochondrial genetics of Opuntia, potentially facilitating future research and breeding programs aimed at enhancing the genetic diversity and adaptability of O. cochenillifera by leveraging its unique mitochondrial genome characteristics.